Color stability of frequently used aesthetic restorative materials following in vitro exposure to chlorhexidine- and octenidine-based mouthrinses - Markus Laky; Stefanie Brandl; Muazzez Arslan; Daniela Boryshchuk; Marta Cześnikiewicz-Guzik; Xiaohui Rausch-Fan; Andreas Moritz; Brenda Laky (BMC Oral Health)
Abstract Background Long-term color match is one of the most important characteristics of aesthetic restorative materials as discoloration constitutes a primary reason for otherwise unnecessary replacements. The aim of the present in vitro study was to evaluate the color stability of frequent dental materials (ceramic, composite, orthodontic adhesive) induced by common antiseptic mouthrinses taking into account black tea consumption and mechanical cleaning. Methods Twenty-four disc-shaped specimens (8 × 2 mm) were made of the materials Ceram.x Spectra™ ST HV, Ceram.x Spectra™ flow, Ceramill® Zolid HT+ PS and Unitek™ Transbond™ LR. Each of the following solutions was tested on six pieces per material: Chlorhexamed forte (CHX), octenident® (OCTD), octenimed® (OCTM) and artificial saliva (control). Dental samples underwent a total of 30 discoloration cycles in which they were alternatively placed into artificial saliva, black tea and respective mouthrinse or only in artificial saliva. After every 10 cycles, discs were mechanically cleaned with toothbrush and toothpaste. After 30 cycles, dental specimens were submitted to professional polishing. Color shifts were measured at different time-points using the VITA Easyshade® V spectrophotometer and displayed as total color difference ∆E (mean ± standard error). A post-hoc Tukey test (⍺ = 0.05) was applied to the mean ∆E values after 30 cycles to determine discoloration discrepancies between various mouthrinses as well as the control. Moreover, photos of individual discs were taken at all measurement times to visualize potential color changes by eye. Results All mouthrinses showed major color shifts in the clinically visible range compared to the control on all different dental materials tested. However, CHX caused significantly more discoloration than OCTM and OCTD. Established color changes could be almost completely removed by simple brushing and even further by professional polishing to clinically acceptable levels on all tested materials. Conclusions Prolonged application of antiseptic mouthrinses may cause discoloration on different restorative materials. To maintain aesthetically satisfying conditions, patients should be educated about the importance of daily mechanical tooth brushing and regular professional polishing.